Valution and Asset Selection Under Alternative Investment Opportunities: Discussion - Pinches, George E. (Journal of Finance, 1976)
George E. Pinches, Valution and Asset Selection Under Alternative Investment Opportunities: Discussion, The Journal of Finance, Vol. 31, No. 2, Papers and Proceedings of the Thirty-Fourth Annual Meeting of the American Finance Association Dallas, Texas December 28-30, 1975 (May, 1976), pp. 546-549